2020
DOI: 10.21203/rs.3.rs-27641/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study on health-related quality of life and influencing factors of pediatric medical staff during the COVID-19 outbreak

Abstract: Aims To evaluate the health-related quality of life (HRQoL) status and explore its associated factors in pediatric medical staff during the COVID-19 epidemic so as to guide hospitals and administrators to formulate suitable interventions.Methods A cross-sectional study was conducted to investigate the HRQoL of pediatric medical staff. Univariable and multivariable logistic regression were used to analyze the associated factors.Results A total of 2,997 participants were recruited. Females scored worse than male… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Despite the significance of the stress-related COVID – 19, data are lacking about its association with health-related quality of life. Thus, there is an utmost need to study the association of stress-related to COVID – 19 with Health-Related Quality of Life (HR-QOL) to assist the policymakers in designing adequate specific preventive interventions/measures to avoid hampering of Health-Related Quality of Life (HR-QOL) among masses ( 12 ). COVID-19 pandemic plays a vital role in exerting psychological and physiological stress on common men & women, social organizations and businesses globally.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significance of the stress-related COVID – 19, data are lacking about its association with health-related quality of life. Thus, there is an utmost need to study the association of stress-related to COVID – 19 with Health-Related Quality of Life (HR-QOL) to assist the policymakers in designing adequate specific preventive interventions/measures to avoid hampering of Health-Related Quality of Life (HR-QOL) among masses ( 12 ). COVID-19 pandemic plays a vital role in exerting psychological and physiological stress on common men & women, social organizations and businesses globally.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with a previous report, as it has been shown that physicians tend to spend more time in areas where patients with SARS-CoV-2 are assisted (36). Furthermore, prolonged shift times, work overload, psychological distress, exposure to probable cases amongst peers could lead physicians to be considered a group with significant occupational risk for developing COVID-19 related outcomes (37)(38)(39).…”
Section: (Which Was Not Certified By Peer Review) Preprintsupporting
confidence: 91%
“…Negatively worded items were then recoded reversely to ensure that higher scores reflect high quality of life or more favorable state of the study participantsand their scores were then averaged to form specific dimensions/ domains i.e. the score of each subscale (domain) is the sum score of its items divided by the number of items (Huang et al, 2020) [15].…”
Section: Discussionmentioning
confidence: 99%